Permeable superabsorbent and method for producing same - Patents.com

The use of X-ray amorphous aluminum hydroxide and controlled water addition during the surface post-crosslinking process addresses absorption capacity and swelling speed issues in super-absorbents, improving fluid penetration and reducing gel blocking in hygienic products.

JP7621328B2Active Publication Date: 2025-01-24BASF SE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022504095
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-24
Filing Date
2020-07-14
Publication Date
2025-01-24
Estimated Expiration
2040-07-14

AI Technical Summary

Technical Problem

Existing super-absorbents face challenges in maintaining high absorption capacity under pressure and swelling speed, particularly in hygienic products, with issues in fluid penetration and gel blocking.

Method used

A method involving the use of X-ray amorphous aluminum hydroxide during the surface post-crosslinking process of super-absorbent polymers, combined with controlled water addition in multiple portions, to enhance penetration and prevent gel blocking.

Benefits of technology

The method results in super-absorbents with improved penetration and absorption under load, reducing gel blocking and enhancing the overall performance in hygienic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621328000001
    Figure 0007621328000001
  • Figure 0007621328000002
    Figure 0007621328000002
Patent Text Reader

Abstract

Highly permeable superabsorbent materials can be prepared by polymerizing an aqueous monomer solution comprising a) at least one ethylenically unsaturated monomer having acidic groups, optionally at least partially in salt form, b) at least one crosslinking agent, c) at least one initiator, d) optionally one or more ethylenically unsaturated monomers copolymerizable with the monomers mentioned under a), and e) optionally one or more water-soluble polymers, drying the resulting polymer, optionally grinding the dried polymer, and sieving the ground polymer, optionally the polymer is prepared by a method comprising the steps of: surface post-crosslinking a dried, optionally ground and sieved polymer; adding, after the drying, grinding or sieving and, if a surface post-crosslinking step is carried out, during or after the surface post-crosslinking step, X-ray amorphous aluminum hydroxide powder; and, after the addition of the X-ray amorphous aluminum hydroxide powder, adding 0.1% to 10% by weight of water, based on the amount of polymer before the addition of the X-ray amorphous aluminum hydroxide powder, wherein the water is added to the superabsorbent in at least three portions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a permeable superabsorbent, a method for producing it, and its uses, as well as to hygiene articles containing it. [Background technology]

[0002] Superabsorbents are known. For such materials the following names are also commonly used, such as "highly swelling polymers", "hydrogels" (often also used in dry form), "hydrogel-forming polymers", "water-absorbing polymers", "absorbent gel-forming materials", "swellable resins", "water-absorbing resins", etc. These materials are crosslinked hydrophilic polymers, more particularly (co)polymerized hydrophilic monomers, graft (co)polymers of one or more hydrophilic monomers on a suitable graft base, crosslinked cellulose ethers or starch ethers, crosslinked carboxymethylcellulose, partially crosslinked polyalkylene oxides, or polymers formed from natural products capable of swelling in aqueous liquids, such as guar derivatives, the most common being water-absorbing polymers based on partially neutralized acrylic acid. An essential property of a superabsorbent is its ability to absorb several times its own weight in aqueous liquids and not release the liquid again even under certain pressure. Superabsorbents used in the form of dry powders transform into gels when they absorb fluids, and likewise into hydrogels when they absorb water in the usual way. Crosslinking is essential for synthetic superabsorbents and is an important difference from conventional simple thickeners, since it makes the polymer insoluble in water. Soluble substances would not be usable as superabsorbents. By far, the most important field of use for superabsorbents is the absorption of body fluids. Superabsorbents are used, for example, in diapers for babies, in incontinence products for adults, or in feminine hygiene products. Other fields of use are, for example, as water retention agents in market gardening, as water storage means for fire protection, for fluid absorption in food packaging, or quite generally for absorbing moisture.

[0003] A superabsorbent is capable of absorbing several times its own weight in water and retaining it under a certain pressure. Generally, such a superabsorbent has a CRC ("centrifuge retention capacity", see test method below) of at least 5 g / g, preferably at least 10 g / g, more preferably at least 15 g / g. A "superabsorbent" may also be a mixture of different individual superabsorbent materials or a mixture of components that exhibit superabsorbent properties only when they interact; what is important here is the properties of the superabsorbent, not the physical composition.

[0004] Important characteristics of a superabsorbent are not only its absorption capacity, but also its ability to retain fluid under pressure (usually expressed as "Absorption under Load" ("AUL") or "Absorption against Pressure" ("AAP"), see below for test methods), and its permeability, i.e. its ability to conduct fluid in the swollen state (usually expressed as "Saline Flow Conductivity" ("SFC") or "Gel Bed Permeability" ("GBP"), see below for test methods (although changes to a superabsorbent do not necessarily change both its SFC and GBP values, or change them to the same extent). Swollen gels can impede or prevent the conduction of fluid to a superabsorbent that is not yet swollen ("gel blocking"). Good fluid conducting properties are possessed, for example, by hydrogels that have high gel strength in the swollen state. A gel with low gel strength is prone to deformation under pressure (body pressure) and blocks pores in the superabsorbent / cellulose fiber absorbent core, thus preventing fluid induction and absorption by the not yet swollen or not fully swollen superabsorbent. An increase in gel strength is generally achieved with a higher degree of crosslinking, which reduces the absorption capacity of the product. An accurate way to increase gel strength is to increase the degree of crosslinking on the surface of the superabsorbent particle compared to the interior of the particle. To this end, superabsorbent particles with an average crosslink density, which are usually dried in a surface postcrosslinking step, are subjected to further crosslinking in a thin surface layer of the particle. The surface postcrosslinking increases the crosslink density in the shell of the superabsorbent particle, which increases the absorbency under compressive stress to a higher level. While the absorption capacity in the surface layers of the superabsorbent particles is reduced, their cores have an improved absorption capacity compared to the shell as a result of the presence of mobile polymer chains, and as a result the shell structure ensures improved permeability without gel blocking occurring.It is likewise known that superabsorbents can be obtained which are generally crosslinked to a relatively high degree, the degree of crosslinking within the particle being subsequently reduced compared to the outer shell of the particle.

[0005] Methods for producing superabsorbents are also known. The most common acrylic acid-based superabsorbents on the market are produced by free radical polymerization of acrylic acid in the presence of a crosslinking agent ("internal crosslinker"), which is neutralized to a certain extent before, after, or partially before and partially after polymerization, typically by adding an alkali, usually aqueous sodium hydroxide solution. The polymer gel thus obtained is pulverized (which can be carried out simultaneously with polymerization, depending on the polymerization reactor used) and dried. The dry powder thus obtained ("base polymer") is typically post-crosslinked on the surface of the particles by reacting it with a further crosslinking agent, such as an organic crosslinking agent or a polyvalent cation, such as aluminum (usually used in the form of aluminum sulfate), or both, in order to obtain a surface layer that is more highly crosslinked compared to the particle interior.

[0006] Fredric L. Buchholz and Andrew T. Graham (editors) in "Modern Superabsorbent Polymer Technology", J. Wiley & Sons, New York, USA / Wiley-VCH, Weinheim, Germany, 1997, ISBN 0-471-19411-5, give a comprehensive overview of superabsorbents, their properties and methods for producing them.

[0007] It is known to treat superabsorbents with aluminum compounds. For example, superabsorbents are covered with inorganic fine particles to reduce the tendency to caking and increase the flowability of the powder or its permeability. Usually, precipitated silicon dioxide is used for this purpose, but US Pat. No. 7,795,345 (B2), US Pat. No. 3,932,322 or WO 2013 / 076031 (A1) also disclose the addition of pyrogenic silicon oxide or aluminum oxide to superabsorbents. According to the teaching of WO 01 / 68156 (A1), aluminosilicates, such as zeolites, are added to superabsorbents to increase permeability and limit unpleasant odors. WO 2007 / 74108 (A1) teaches coating superabsorbents with non-reactive and non-film-forming compounds, such as water-insoluble salts. Hydrated aluminum oxide is mentioned among several such salts. WO 2007 / 121941 A2 discloses a similar superabsorbent coated with an inorganic powder, where the powder may also contain a binder. Aluminium hydroxide is mentioned among several inorganic powders.

[0008] Although it is very rarely carried out, it is also known to use polyvalent cations, such as aluminum, as the internal crosslinking agent of superabsorbents.In contrast, it is customary to add polyvalent cations to superabsorbents during surface postcrosslinking using a surface postcrosslinking agent that forms covalent bonds between polymer chains.

[0009] WO 99 / 55767(A1) describes a compound of formula M n [H 2n+2 AlnO 3n+1], M=K or Na, and n=an integer between 1 and 10. WO 98 / 48857 A1 describes superabsorbents crosslinked with Al, Fe, Zr, Mg, or Zn cations and then mixed with a liquid, such as water, mineral oil, or a polyol. WO 01 / 74913 A1 relates to the regeneration of superabsorbents, specifically to increasing the permeability lost due to abrasion, by adding a solution of at least a trivalent cation, typically an aqueous solution of aluminum sulfate. US Pat. No. 6,620,889 B1 discloses superabsorbents that are surface postcrosslinked with a combination of a polyol and a salt of a polyvalent metal in an aqueous solution. The anion of the salt may be chloride, bromide, sulfate, carbonate, nitrate, phosphate, acetate, or lactate. The use of aluminum sulfate is preferred.

[0010] According to the teachings of WO 2006 / 111402(A2), the base polymer is treated with a permeability enhancer selected from silicon-oxygen compounds, salts of polyvalent, especially trivalent, cations, or mixtures thereof. The salts of trivalent cations are preferably aluminum salts, selected from the group of salts including aluminum lactate, aluminum oxalate, aluminum citrate, aluminum glyoxylate, aluminum succinate, aluminum tartrate, and other organic and inorganic aluminum salts. WO 2005 / 108472(A1) discloses a method comprising treating the base polymer with a water-soluble salt of a polyvalent metal and an organic acid or salt thereof. The salt of the polyvalent metal is preferably aluminum sulfate. The organic acid or salt thereof is selected from the group of acids including citric acid, glyoxylic acid, glutaric acid, succinic acid, tartaric acid, lactic acid, and the alkali metal or ammonium salts of these acids.

[0011] WO 2004 / 113452 A1 describes superabsorbents treated with concentrated solutions of polyvalent metal salts, especially sodium aluminate. WO 2013 / 156281 A1 teaches the treatment of superabsorbents with aluminum glycinate. WO 2010 / 108875 A1, WO 2012 / 045705 A1, and WO 2013 / 156330 A1 teach the treatment of superabsorbents with basic aluminum salts, such as basic aluminum acetate or aluminum lactate.

[0012] WO 2009 / 080611 A2 discloses the treatment of superabsorbents with a mixture of aluminum salts, one of which contains a chelating anion, such as a dicarboxylate or hydroxycarboxylate anion, with the lactate anion being particularly preferred, and the other is a weakly complexing anion, such as chloride, nitrate, sulfate, hydrogen sulfate, carbonate, hydrogen carbonate, nitrate, phosphate, hydrogen phosphate, dihydrogen phosphate, or carboxylate, with the sulfate anion being particularly preferred. Prior European Patent Office application No. 17200963.1 teaches superabsorbents which form a complex with aluminum ions, which are applied in the form of an aqueous solution containing aluminum ions (optionally Al 2 O 3 ), in a proportion in the range of 0.5% by weight to 15% by weight, based on the total mass of the solution. 3+ (which can be converted to Al), and further contains anions of lactic acid (lactate ions) and phosphoric acid (phosphate ions), wherein the molar ratio of lactate ions is Al 3+ The molar ratio of the phosphate ion is in the range of 0.01 to 2.99 times the molar amount of Al. 3+ The molar amount of the solution ranges from 0.01 to 2.99 times the molar amount of the solution. These solutions are prepared by adding acid to amorphous aluminum hydroxide.

[0013] EP 233067 A2 discloses the surface postcrosslinking of superabsorbents using aluminum salts capable of reacting with the superabsorbents in the presence of polyols and water. Among several aluminum salts, aluminum hydroxide is also mentioned. The use of freshly precipitated aluminum hydroxide sol or gel is recommended. According to the teaching of US Pat. No. 5,145,906, the undried polymeric gel is treated with a surface postcrosslinker, and the surface postcrosslinking reaction occurs during heating to dryness or during drying. Aluminum hydroxide is one of the possible mentioned surface postcrosslinkers. JP 09 / 124879 also mentions aluminum hydroxide among several compounds for this purpose, which, like the other water-soluble compounds mentioned, is to be applied as a solution. EP 780424 A1 mentions several metal hydroxides and chlorides, including aluminum, as surface postcrosslinkers. U.S. Patent No. 5,684,106 refers to aluminum sulfate, sodium aluminate, or other polyvalent metal compounds for this purpose. Japanese Patent No. 3121934 refers to aluminum sulfate, sodium aluminate, or other polyvalent metal compounds for this purpose. 3 ] n AlCl 3 and n=10-21.

[0014] WO 03 / 049778 A1 teaches that in the case of superabsorbents postcrosslinked either with covalent surface postcrosslinkers or with polyvalent metal ions, after the first absorption of liquid, the postcrosslinks are redissolved using metal ions, e.g. complexing agents, thus obtaining further absorption capacity. Aluminum hydroxide is mentioned as a postcrosslinker among several possible polyvalent metal salts.

[0015] According to the teaching of WO 2012 / 143215 A1, a solution of a neutralized polyvalent metal salt, preferably a solution of an aluminum salt formed from an aluminum compound and an organic acid having a chelating anion, neutralized with an acid or base to a pH of 5 to 9, is added to the superabsorbent. The aluminum compound thus reacted with an acid having a chelating anion may also be aluminum hydroxide. The organic chelating anions mentioned form water-soluble complexes with the metal ions. WO 2013 / 72311 A1 teaches surface postcrosslinking using a metal salt, for example aluminum hydroxide, and a complex of 2-hydroxycarboxamide.

[0016] WO 2014 / 167036 A1, WO 2014 / 167040 and WO 2014 / 168858 A1, like EP 233067 A2 already mentioned above, disclose the application of freshly precipitated aluminium hydroxide sols in surface postcrosslinking.

[0017] US 2016 / 0235882 A1 teaches mixing aluminum hydroxide powder into the superabsorbent base polymer before applying a solution of a covalent post-crosslinker. The mixing is preferably carried out in dry form, since there is an increased tendency for caking when applying a suspension.

[0018] International patent application PCT / EP2019 / 058165, filed on April 1, 2019 by the same applicant, discloses adding x-ray amorphous aluminum hydroxide powder to a superabsorbent. Optionally, 0.1% to 10% by weight of water is added to the superabsorbent, based on the amount of polymer before adding the x-ray amorphous aluminum hydroxide powder. Summary of the Invention [Problem to be solved by the invention]

[0019] The problem remains to find a different or even improved superabsorbent, in particular a permeable superabsorbent, or a significantly simplified or improved method for producing them. The use properties of the superabsorbent, in particular its absorption capacity for liquids, including under pressure, and its swelling rate, quantified as volumetric absorbency under pressure "VAUL", should be at least only slightly deteriorated, if at all. Further objects of the invention are the use of this superabsorbent, for example hygiene products comprising this superabsorbent, and the method for producing it. [Means for solving the problem]

[0020] The object is to provide a method for producing a superabsorbent, comprising the steps of: a) at least one ethylenically unsaturated monomer having an acidic group, optionally at least partially in salt form; b) at least one crosslinking agent; c) at least one initiator; d) optionally one or more ethylenically unsaturated monomers copolymerizable with the monomers mentioned under a), and e) optionally, one or more water-soluble polymers; polymerizing an aqueous monomer solution comprising drying the resulting polymer; Optionally, grinding the dried polymer and sieving the ground polymer; surface postcrosslinking the optionally dried, optionally ground and sieved polymer, adding X-ray amorphous aluminum hydroxide powder after drying, grinding or sieving, and during or after the surface postcrosslinking step if this step is carried out, adding 0.1% to 10% by weight of water based on the amount of polymer before adding the X-ray amorphous aluminum hydroxide powder after adding the X-ray amorphous aluminum hydroxide powder; Water is added to the superabsorbent in at least three portions, This was achieved by the method.

[0021] The superabsorbents according to the invention are obtainable and preferably produced by the process according to the invention. They surprisingly exhibit good permeability without significant deterioration of other use properties, such as CRC or AUL.

[0022] Additionally, articles for absorbing fluids, in particular hygienic articles for absorbing fluid exudates or fluid components of exudates, have been found which comprise the superabsorbent of the present invention.Methods for producing such articles for absorbing fluids have also been found, the production of which involves the step of adding the superabsorbent of the present invention to the article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In the preparation of the inventive superabsorbent in the inventive process, X-ray amorphous aluminium hydroxide is added.

[0024] The addition of polyvalent metal salts to superabsorbents has been known for a long time. Usually, aluminum salts are added. The addition is typically carried out during the step of surface postcrosslinking with covalent surface postcrosslinkers, i.e. compounds capable of forming covalent bonds with functional groups on the surface of the superabsorbent particles, typically the acid groups of conventional acrylic acid-based superabsorbents. Finally, the addition of polyvalent metal salts also results in crosslinking sites at the surface of the superabsorbent particles, albeit by ionic bonds. The treatment of superabsorbents with polyvalent metal ions during surface postcrosslinking is often called "complexation". Thus, "complexation" is, strictly speaking, just a special term for the special case of surface postcrosslinking, in which polyvalent metal ions create ionic bonds between some polar groups on the surface of the superabsorbent particles, and complexation is often also discussed under "surface postcrosslinking". In the context of the present invention, "complexation" is understood to mean surface postcrosslinking with polyvalent metal ions (especially aluminum), in order to distinguish it from surface postcrosslinking with postcrosslinkers that form covalent bonds with polar groups on the surface of the superabsorbent particles.

[0025] In the complexation, the added metal salt reacts with the superabsorber. Therefore, the X-ray amorphous aluminum hydroxide added here to the superabsorber according to the invention is not maintained as such in the superabsorber, or at least not completely. Therefore, what is essential is that the superabsorber of the invention is treated with X-ray amorphous aluminum hydroxide, or in other words, that it is added to the superabsorber of the invention. It may still contain the added X-ray amorphous aluminum hydroxide, but it does not have to be so.

[0026] Aluminum hydroxide is understood here to mean aluminum trihydroxide. This nomenclature is not uniformly treated in the literature. More precisely, aluminum hydroxide is also often considered as one of the aluminum hydroxide hydrates or called hydrated aluminum oxide. Aluminum hydroxide is precipitated in a known manner from aluminum salt solutions by adding bases in each case up to a neutral pH range, or from aluminic acid solutions by adding acids. To prepare amorphous aluminum hydroxide, crystalline γ-Al(OH) is used, if the precipitation is slow. 3 ("hydrargillite" or "gibbsite") is formed from an aluminate solution or α-Al(OH) 3Precipitation must be rapid, since hydrated aluminum hydroxide ("Bayerite") is formed from the aluminum salt solution. Bayerite slowly transforms over time into hydrargillite. These hydroxides can slowly condense to form aluminum hydroxide hydrates (diaspore or boehmite) of formula Al(O)OH, also sometimes called "hydroxides". Thus, in the production of X-ray amorphous aluminum trihydroxide, rather than seeding with crystalline aluminum hydroxide as in the Bayer process of preparing aluminum hydroxide hydrate, there is rapid precipitation and rapid drying. It is preferred to dry the freshly precipitated aluminum hydroxide gel by spray drying. The chemical properties and preparation of aluminum hydroxide, aluminum oxide hydrate and aluminum oxide are well known, see for example Holleman / Wiberg, Lehrbuch der Anorganischen Chemie [Inorganic Chemistry], Walter de Gruyter & Co., Berlin, 103rd edition, 2016, ISBN 978-3-11-051854-2, chapter 2.4 "Sauerstoffverbindungen des Aluminiums" [Oxygen Compounds of Aluminum], or Ullmann's Encyclopedia of Industrial Chemistry, "Aluminum Oxide", Wiley-VCH Verlag Gmbh & Co.KGaA, Weinheim 2012, DOI 10.1002 / 14356007.a01_557. Some structural differences between amorphous and crystalline aluminium hydroxide at the atomic / molecular level are explained by T. Isobe et al., J. Colloid and Interface Science 261 (2003) 320-324, which additionally refers by way of preface to known methods of producing amorphous aluminium hydroxide.Powdered X-ray amorphous aluminum hydroxide is also commercially available, for example, as "Aluminum Hydroxide Dry Gel" from Dr. Paul Lohmann GmbH KG, Hauptstrasse 2, 31860 Emmerthal, Germany, catalog number 511066100.

[0027] Aluminum hydroxide is X-ray amorphous if it does not show a signal ("line") in the X-ray powder diffractogram. Crystalline materials diffract electromagnetic radiation with wavelengths on the order of the interatomic distance, and X-ray radiation is typically used, so that the diffraction pattern of the radiation can be measured. If single crystals are large enough, they give rise to a diffraction pattern in the form of dots, where the crystal structure, including the positions of the atoms in the crystal lattice, can be calculated from the positions and intensities of the dots. It is possible to measure the diffractogram for a powder of a crystalline material, which shows as a signal ("line") a maximum of the scattered X-ray radiation as a function of the turning angle, where the half-width of the maximum correlates with the size of the crystals in the powder. All this is well known, see for example Ullmann's Encyclopedia of Industrial Chemistry, "Structure Analysis by Diffraction", Wiley-VCH Verlag GmbH & Co.KGaA, Weinheim 2012, DOI 10.1002 / 14356007.b05_341. The methods are well established and instruments for measuring powder diffraction patterns are commercially available.

[0028] Thus, if the powder does not have a crystalline structure, it will not show a signal in the X-ray diffraction pattern, so that the atoms or molecules are in a completely or largely disordered form, or the crystals are so small that the number of unit cells in the crystals that align to form a crystal is insufficient for focused diffraction of radiation, and the half-width of the maximum in the diffraction pattern becomes so large that they disappear in the baseline and only scattered radiation can be measured. What is critical here is not the particle size of the powder, but the size of the crystals in the powder. In one powder particle, many smaller crystals ("primary crystals" or "primary crystallites") can be aggregated or combined in some other way. With respect to the X-ray amorphous aluminum hydroxide used herein according to the invention, the primary crystallites present therein, if any, have a size of 2 nm or less.

[0029] X-ray amorphous aluminum hydroxide can be used in a mixture with crystalline aluminum hydroxide. In this case, lines due to the crystalline component may occur in the diffraction pattern of the mixture. The proportion of crystalline aluminum hydroxide can also be determined by calibrating the powder diffraction pattern, for example by adding a known amount of crystalline aluminum hydroxide to a powder comparison sample and showing that the total area of ​​all lines in the resulting diffraction pattern is increased relative to the area of ​​all lines in the diffraction pattern of the actual sample. All this is known and is no different from, for example, chromatographic calibration.

[0030] Generally, the total aluminium hydroxide added has a proportion by weight of at least 50%, preferably at least 70%, more preferably at least 90% x-ray amorphous aluminium hydroxide. Pure x-ray amorphous aluminium hydroxide free of crystalline components occurring in the x-ray diffraction pattern, or at least aluminium hydroxide consisting solely of x-ray amorphous aluminium hydroxide apart from unavoidable small crystalline fractions (such as may occur during ageing), is preferred.

[0031] According to the invention, X-ray amorphous aluminum hydroxide is generally added in an amount of at least 0.01% by weight, preferably at least 0.1% by weight, more preferably at least 0.2% by weight, even more preferably at least 0.3% by weight, and generally at most 1% by weight, preferably at most 0.8% by weight, more preferably at most 0.7% by weight, even more preferably at most 0.5% by weight, in each case based on the superabsorber before addition. One advantage of the present invention over the teachings of International Patent Application PCT / EP2019 / 058165 is that less aluminum hydroxide is needed to achieve a similar enhancement of GBP.

[0032] According to the present invention, X-ray amorphous aluminum hydroxide is added as powder after drying, grinding or sieving, and during or after surface post-crosslinking if surface post-crosslinking is performed.The total amount of X-ray amorphous aluminum hydroxide added can also be divided into several addition sites or times.Addition to one site and one time is preferred.

[0033] In the method of the present invention, the X-ray amorphous aluminum hydroxide is therefore dry mixed into the superabsorbent powder after drying, and if a sieve fraction of the superabsorbent is obtained after drying, it is passed to a step of sieving. This can be carried out by any known mixing device and method, preferably in a mixer with moving mixing equipment, for example a screw mixer, a disk mixer, a paddle mixer or a shovel mixer, or a mixer with other mixing equipment. Suitable mixers are available, for example, as Pflugschar® (Ploughshare) mixers from Gebr.Loedige Maschinenbau GmbH, Elsener-Strasse 7-9, 33102 Paderborn, Germany.

[0034] According to the present invention, after the X-ray amorphous aluminum hydroxide is mixed, the superabsorbent thus produced is moistened, i.e. its moisture is increased.For this purpose, in a dedicated device or conveniently in the same mixer, water is added, for example, by spray application through a nozzle, similar to the manner described below by spray application of a postcrosslinker solution.In general, water is added to the superabsorbent in an amount of at least 0.1% by weight, preferably at least 0.5% by weight, more preferably at least 1% by weight, and generally at most 10% by weight, preferably at most 7% by weight, more preferably at most 5% by weight, in each case based on the superabsorbent before addition.

[0035] According to the invention, water is added to the superabsorbent in at least three portions, meaning that the total amount of water is not added at one time, but at least three portions at different times, and the superabsorbent is preferably mixed between the addition of each portion of water.

[0036] Typically, the second and subsequent portions of water are added after a time generally of at least 1 second, for example at least 5 seconds, at least 10 seconds, at least 15 seconds, at least 20 seconds or at least 40 seconds after the complete addition of the previous portion. The optimal time between additions can be easily determined for any given superabsorbent and mixing conditions by a few routine experiments. If a shorter or longer time before adding the next portion of water does not further improve the properties of the superabsorbent, there is no need to shorten or extend such time. Very gentle mixing may require a longer time between the addition of water. In general, once a time long enough to achieve the desired increase in properties, especially GBP, a longer time between the addition of each portion of water will not further improve the superabsorbent, but will not worsen either the superabsorbent or its properties, as compared to adding all the water at once in one amount. Thus, the time between the addition of the first and second portions and subsequent portions of water is not critical and can be selected according to commercial aspects and what is achievable using the available equipment. Typically, while shorter times are commercially preferred, available mixing equipment may require longer times to mix the superabsorbent. In standard commercial powder mixing equipment, the time is generally at most 60 minutes, preferably at most 3 minutes, more preferably at least 2 minutes after the addition of the previous charge, for example 1 minute after the addition of the previous charge.

[0037] Water is added in at least three portions. Preferably, water is added in at least four portions. Water can be added in any number of portions greater than four, such as five, six, seven, eight, nine, ten or more portions. These portions of water may or may not be equal in amount. Preferably, the total amount of water is added in equal portions.

[0038] For every specific superabsorbent produced according to the method of the present invention, there exists a number of portions that does not bring about any further increase in technical benefits.This number can be easily determined by routine experimentation.Although it is possible and in some cases even reasonable to add water in portions more than the minimum necessary to achieve the desired effect of strengthening GBP, for example due to the constraints of existing equipment, it is generally economically disadvantageous to use more than the minimum number of portions.

[0039] The addition of water in small portions can be easily carried out in a batch process by adding water in small portions to a quantity of superabsorbent in a container, preferably a stirred container. More preferably, water is added to the superabsorbent in a container, where the superabsorbent is continuously flowing or transported in the container. Even more preferably, the superabsorbent is also stirred in this container. Water may be added in the same type of equipment used to add aluminum hydroxide, and conveniently, it may be added in exactly the same equipment used to add aluminum hydroxide. Most conveniently, each portion of water is sprayed onto the mixed superabsorbent through a nozzle, similar to the manner described below by spray application of the postcrosslinker solution.

[0040] In a continuous operation device, the superabsorbent advances continuously through the device, and adding each quantity of water to the superabsorbent at different times separately from each other is equivalent to adding each quantity of water at different places along the entire path of advancement of the superabsorbent, so that each quantity of water reaches the superabsorbent moving in one shot at different times during the superabsorbent's advancement through the device. In other words, the fact that each quantity of water can be sprayed continuously and permanently at the same time from the nozzles still means that these quantities are added separately to the superabsorbent if the nozzles are located at positions distant from each other along the path of advancement of the superabsorbent. Thus, adding water in small portions can be achieved by spacing the nozzles accordingly in the device so that each quantity of water is added at a desired time interval of the total residence time of the superabsorbent particles in the device. In a mixing device, the average residence time of the particles is important. Methods for determining the average residence time of the particles in a particular continuous device are known, and one convenient method is to add samples of particles of different colors as main amounts and determine the time when the number of particles of different colors in the total particles discharged from the device reaches a maximum. According to the present invention, water can be added in small portions easily by positioning nozzles for water addition along the length of the continuous device. At one location along the length of the device, one portion of water is delivered. One portion of water may be added through two or more nozzles positioned at that location along the length of the device. As the superabsorbent travels through the continuous device, it will reach the next nozzle location along the length of the device at a later time, so that the next portion of water is added at a later time. In this embodiment of the present invention, the number of nozzle locations along the length of the device is equal to the number of portions of water to be added, and the distance between the nozzle locations along the length of the device, together with the average residence time of the particles, determines the time at which each portion of water is added. In other words, nozzles are positioned along the length of the device, where each portion of water is added at a desired time in view of the average residence time of the superabsorbent in the particular device.

[0041] If the superabsorbent is not warm or hot at the time of adding the water (e.g. after the drying operation described above), it may be convenient to add heated water in this re-moisturizing operation. Generally, the water is added at a temperature of at least 5° C., preferably at least 20° C., more preferably at least 25° C., for example at a temperature of 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., or 90° C. It is also possible to use steam.

[0042] Addition of X-ray amorphous aluminum hydroxide and optional addition of water can be carried out before, during or after surface postcrosslinking.When the applied surface postcrosslinker solution contains water, it is convenient to carry out addition of X-ray amorphous aluminum hydroxide beforehand, and then add water in a quantity other than the last quantity, and replace the addition of the last quantity of water with the addition of surface postcrosslinker solution.

[0043] Among other things, an inventive method for producing a superabsorbent is known, which comprises the steps of: a) at least one ethylenically unsaturated monomer having at least one acidic group, optionally at least partially in salt form; b) at least one crosslinking agent; c) at least one initiator; d) optionally one or more ethylenically unsaturated monomers copolymerizable with the monomers mentioned under a), and e) optionally, one or more water-soluble polymers; The present invention relates to a method for aqueous polymerization of a monomer mixture comprising the steps of:

[0044] The monomers a) are preferably water-soluble, thus their solubility in water at 23° C. is typically at least 1 g / 100 g water, preferably at least 5 g / 100 g water, more preferably at least 25 g / 100 g water and most preferably at least 35 g / 100 g water.

[0045] Suitable monomers a) are, for example, ethylenically unsaturated carboxylic acids or their salts, such as acrylic acid, methacrylic acid, maleic acid or its salts, maleic anhydride, and itaconic acid or its salts.Particularly preferred monomers are acrylic acid and methacrylic acid.Acrylic acid is very particularly preferred.

[0046] Further suitable monomers a) are, for example, ethylenically unsaturated sulfonic acids, such as styrenesulfonic acid and 2-acrylamido-2-methylpropanesulfonic acid (AMPS).

[0047] Impurities can have a significant effect on the polymerization. The raw materials used should therefore have maximum purity. It is therefore often advantageous to specially purify the monomer a). Suitable purification methods are described, for example, in WO 2002 / 055469 A1, WO 2003 / 078378 A1 and WO 2004 / 035514 A1. A suitable monomer a) is, for example, acrylic acid, which is purified according to WO 2004 / 035514 A1 and contains 99.8460% by weight of acrylic acid, 0.0950% by weight of acetic acid, 0.0332% by weight of water, 0.0203% by weight of propionic acid, 0.0001% by weight of furfural, 0.0001% by weight of maleic anhydride, 0.0003% by weight of diacrylic acid and 0.0050% by weight of hydroquinone monomethyl ether.

[0048] The proportion of acrylic acid and / or its salts in the total amount of monomers a) is preferably at least 50 mol %, more preferably at least 90 mol %, most preferably at least 95 mol %.

[0049] The monomer solution preferably comprises at most 250 ppm by weight, preferably at most 130 ppm by weight, more preferably at most 70 ppm by weight, preferably at least 10 ppm by weight, more preferably at least 30 ppm by weight, in particular about 50 ppm by weight of hydroquinone monoether, in each case based on the non-neutralized monomer a), the neutralized monomer a), i.e. the salt of monomer a), being considered for calculation purposes to be the non-neutralized monomer.For example, the monomer solution can be prepared by using an ethylenically unsaturated monomer having an acid group together with the appropriate content of hydroquinone monoether.

[0050] Preferred hydroquinone monoethers are hydroquinone monomethyl ether (MEHQ) and / or α-tocopherol (vitamin E).

[0051] Suitable crosslinking agents b) are compounds that have at least two groups suitable for crosslinking. Such groups are, for example, ethylenically unsaturated groups that can undergo free radical polymerization into polymer chains and functional groups that can form covalent bonds with the acidic groups of monomer a).In addition, polyvalent metal salts that can form coordinate bonds with at least two acidic groups of monomer a) are also suitable as crosslinking agents b).

[0052] The crosslinking agent b) is preferably a compound having at least two polymerizable groups capable of free radical polymerization into a polymer network. Suitable crosslinking agents b) are, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, polyethylene glycol diacrylate, allyl methacrylate, trimethylolpropane triacrylate, triallylamine, tetraallylaminium chloride, tetraallyloxyethane as described in EP 530438 A1, EP 547847 A1, EP 559476 A1, EP 632068 A1, WO 93 / 21237 A1, WO 2003 / 104299 A1, WO 2004 / 104299 A1, WO 2005 / 104299 A1, WO 2006 / 104299 A1, WO 2007 / 104299 A1, WO 2009 ... di- and triacrylates, as described in WO 03 / 104300 A1, WO 2003 / 104301 A1 and DE 10331450 A1, mixed acrylates which contain further ethylenically unsaturated groups as well as acrylate groups, as described in DE 10331456 A1 and DE 10355401 A1, or crosslinker mixtures, as described, for example, in DE 19543368 A1, DE 19646484 A1, WO 90 / 15830 A1 and WO 2002 / 32962 A2.

[0053] Preferred crosslinking agents b) are pentaerythrityl triallyl ether, tetraallyloxyethane, methylene bismethacrylamide, 15-20 tuply ethoxylated trimethylolpropane triacrylate, 15-20 tuply ethoxylated glyceryl triacrylate, 4-45-CH 2 CH 2 O units, polyethylene glycol diacrylate, trimethylolpropane triacrylate, and triallylamine.

[0054] Very particularly preferred crosslinkers b) are polyethoxylated and / or propoxylated glycerols, which are esterified with acrylic or methacrylic acid to give di- or triacrylates, as described, for example, in WO 2003 / 104301 A1. Di- and / or triacrylates of 3- to 10-stilt ethoxylated glycerol are particularly advantageous. Di- or triacrylates of 1- to 5-stilt ethoxylated and / or propoxylated glycerol are very particularly preferred. Most preferred are 3- to 5-stilt ethoxylated triacrylates and / or propoxylated glycerol, especially 3-stilt ethoxylated glycerol triacrylates.

[0055] The amount of crosslinker b) is preferably 0.05% to 1.5% by weight, more preferably 0.1% to 1% by weight, most preferably 0.3% to 0.6% by weight, based in each case on monomer a). With increasing crosslinker content, the centrifuge retention capacity (CRC) decreases and the absorbency under load (AUL) increases.

[0056] The initiators c) used are all compounds that generate free radicals under polymerization conditions, such as thermal initiators, redox initiators, and / or photoinitiators.Suitable redox initiators are sodium peroxodisulfate / ascorbic acid, hydrogen peroxide / ascorbic acid, sodium peroxodisulfate / sodium hydrogen sulfite, and hydrogen peroxide / sodium hydrogen sulfite.The use of mixtures of thermal initiators and redox initiators, such as sodium peroxodisulfate / hydrogen peroxide / ascorbic acid, is preferred. However, the reducing component used is also preferably a sulfonic acid derivative, for example a mixture of the sodium salt of 2-hydroxy-2-sulfinatoacetic acid, the disodium salt of 2-hydroxy-2-sulfonatoacetic acid and sodium hydrogen sulfite, available, for example, under the name BRUGGOLIT® FF6M or BRUGGOLIT® FF7, or alternatively under the name BRUGGOLITE® FF6M or BRUGGOLITE® FF7, for example, from L. Brueggemann KG (Salzstrasse 131, 74076 Heilbronn, Germany, www.brueggemann.com), or the disodium salt of 2-hydroxy-2-sulfonatoacetic acid, available, for example, under the name BLANCOLEN® HP, from L. Brueggemann KG. The initiators are used in customary amounts, in this respect. The customary amount of the reducing component of the redox initiator is generally at least 0.00001% by weight, preferably at least 0.0001% by weight, more preferably at least 0.001% by weight, and generally at most 0.2% by weight, preferably at most 0.1% by weight, in each case based on the amount of monomers a) and d). However, if the only reducing component used in the redox initiator is a sulfonic acid derivative, its amount added is generally at least 0.001% by weight, preferably at least 0.01% by weight, more preferably at least 0.03% by weight, and generally at most 1.0% by weight, preferably at most 0.3% by weight, more preferably at most 0.2% by weight, in each case based on the amount of monomers a) and d). The customary amount of the oxidizing component of the redox initiator is generally at least 0.0001% by weight, preferably at least 0.01% by weight, more preferably at least 0.03% by weight, and generally at most 1.0% by weight, preferably at most 0.3% by weight, more preferably at most 0.2% by weight, in each case based on the amount of monomers a) and d). Amount %, more preferably at least 0.001% by weight, and generally at most 2% by weight, preferably at most 1.0% by weight. A conventional amount of thermal initiator is generally 0.01% by weight, more preferably at least 0.1% by weight, and generally at most 2% by weight, preferably at most 1.0% by weight, in each case based on the amount of monomers a) and d). A conventional amount of photoinitiator is generally 0.001% by weight, more preferably at least 0.01% by weight, and generally at most 1.0% by weight, preferably at most 0.2% by weight, in each case based on the amount of monomers a) and d).

[0057] Ethylenically unsaturated monomers d) which can be copolymerized with the ethylenically unsaturated monomers a) carrying an acidic group are, for example, acrylamide, methacrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, dimethylaminoethyl methacrylate, dimethylaminoethyl acrylate, dimethylaminopropyl acrylate, diethylaminopropyl acrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, maleic acid or its salts, and maleic anhydride.

[0058] The water-soluble polymers e) used may be polyvinyl alcohol, polyvinylpyrrolidone, starch, starch derivatives, modified celluloses such as methylcellulose or hydroxyethylcellulose, gelatin, polyglycols or polyacrylic acids, preferably starch, starch derivatives and modified celluloses.

[0059] Typically, an aqueous monomer solution is used. The water content of the monomer solution is preferably 40% by weight to 75% by weight, more preferably 45% by weight to 70% by weight, and most preferably 50% by weight to 65% by weight. Furthermore, it is possible to use a monomer suspension, i.e., a supersaturated monomer solution. If the water content increases, the energy consumption in the subsequent drying increases, and if the water content decreases, the polymerization heat cannot be sufficiently removed.

[0060] To function optimally, the preferred polymerization inhibitors require dissolved oxygen. Thus, the monomer solution can be inerted, i.e., flushed with an inert gas, preferably nitrogen or carbon dioxide, to remove dissolved oxygen prior to polymerization. The oxygen content of the monomer solution is preferably reduced to less than 1 ppm by weight, more preferably less than 0.5 ppm by weight, and most preferably less than 0.1 ppm by weight prior to polymerization.

[0061] The monomer mixture may contain further components. Examples of further components used in such monomer mixtures are, for example, chelating agents to keep metal ions in solution, or inorganic powders to increase the firmness of the superabsorbent in the swollen state, or undersize recycled from a subsequent grinding operation. All known additives to monomer mixtures can be used here. Only "solution" is discussed here with respect to the monomer mixture, but this also means the polymerization of a suspension, for example when insoluble constituents are added to the monomer mixture.

[0062] The acid groups of the polymer gel resulting from the polymerization are typically partially neutralized. Neutralization is preferably carried out at the monomer stage, in other words a salt of a monomer having an acid group, or more precisely a mixture of a monomer having an acid group and a salt of a monomer having an acid group ("partially neutralized acid") is used as component a) during the polymerization. This is typically accomplished by mixing a neutralizing agent, either as an aqueous solution or preferably also as a solid, into the monomer mixture intended for polymerization, preferably into the monomer having an acid group or into a solution thereof. The degree of neutralization is preferably 25-95 mol%, more preferably 50-80 mol%, most preferably 65-72 mol%, for which customary neutralizing agents can be used, preferably alkali metal hydroxides, alkali metal oxides, alkali metal carbonates or alkali metal hydrogen carbonates, as well as mixtures thereof. Instead of the alkali metal salts, it is also possible to use ammonium salts. Particularly preferred alkali metals are sodium and potassium, but very particular preference is given to sodium hydroxide, sodium carbonate or sodium hydrogen carbonate, as well as mixtures thereof.

[0063] However, it is also possible to carry out the neutralization after polymerization, at the stage where the polymer gel is formed during polymerization. It is also possible to neutralize up to 40 mol %, preferably 10-30 mol %, more preferably 15-25 mol % of the acidic groups by adding a part of the neutralizing agent directly to the monomer solution before polymerization and adjusting only the desired final degree of neutralization at the polymer gel stage after polymerization. If the polymer gel is at least partially neutralized after polymerization, the polymer gel is preferably pulverized mechanically, for example with an extruder, in which case the neutralizing agent may be sprayed, sprinkled, injected and then carefully mixed. For this purpose, the gel material obtained can be extruded several more times to homogenize it.

[0064] However, it is preferred to carry out the neutralization at the monomer stage. In other words, in a very particularly preferred embodiment, the monomers a) used are a mixture of 25-95 mol %, more preferably 50-80 mol %, most preferably 65-75 mol % of salts of monomers with acidic groups and the remaining part, relative to 100 mol %, of monomers with acidic groups. This mixture is, for example, a mixture of sodium acrylate and acrylic acid or a mixture of potassium acrylate and acrylic acid.

[0065] In a preferred embodiment, the neutralizing agent used for neutralization is one that generally has an iron content of less than 10 ppm by weight, preferably less than 2 ppm by weight, more preferably less than 1 ppm by weight. Similarly, it is desirable that the content of chloride and anions of chlorine oxyacids is low. Suitable neutralizing agents are, for example, 50% by weight aqueous sodium hydroxide or potassium hydroxide solutions typically marketed as "membrane grade", and even purer, equally suitable but more expensive, 50% by weight aqueous sodium hydroxide or potassium hydroxide solutions typically marketed as "amalgam grade" or "mercury process".

[0066] Methods for producing superabsorbents from monomer mixtures, such as those described above as examples, are known in principle. Suitable polymerization reactors are, for example, kneading reactors or belt reactors. In kneaders, the polymer gel formed in the polymerization of the aqueous monomer solution or suspension is continuously pulverized, for example by counter-rotating agitator shafts, as described in WO 2001 / 38402 A1. Polymerization on a belt is described, for example, in EP 955086 A2, DE 3825366 A1, and US Pat. No. 6,241,928. Polymerization in a belt reactor forms a polymer gel that must be pulverized in a further processing step, for example in a meat grinder, extruder, or kneader, as in the similarly known polymerization in batch operation or tubular reactors, as described, for example, in EP 445619 A2 and DE 19846413 A1. It is also possible to produce spherical or differently shaped superabsorbent particles by suspension or emulsion polymerization, as described, for example, in EP 457660 A1, or by spray or drop polymerization methods, as described, for example, in EP 348180 A1, EP 816383 A1, WO 96 / 40427 A1, U.S. Pat. No. 4,020,256, U.S. Pat. No. 2002 / 0193546 A1, DE 3519013 A1, DE 102005044035 A1, WO 2007 / 093531 A1, WO 2008 / 086976 A1 or WO 2009 / 027356 A1. Methods in which a monomer mixture is applied to a substrate, for example a nonwoven web, and polymerized, as described, for example, in WO 02 / 94328 A2 and WO 02 / 94329 A1, are likewise known.

[0067] Optionally, in a known manner, sulfonic acid derivatives, including sulfites or sulfinic acid derivatives in admixture, can be added to the superabsorbent or otherwise monomer mixture before or after drying, preferably before drying. For example, these mixtures are standard commercial products and are available under the names BRUGGOLIT® FF6M or BRUGGOLIT® FF7, or alternatively under the names BRUGGOLITE® FF6M or BRUGGOLITE® FF7, from L. Brueggemann KG (Salzstrasse 131, 74076 Heilbronn, Germany, www.brueggemann.com) in the form of a mixture of the sodium salt of 2-hydroxy-2-sulfinatoacetic acid, the disodium salt of 2-hydroxy-2-sulfonatoacetic acid, and sodium hydrogen sulfite. The use of sulfonic acid derivatives in pure form is preferred. These are also standard commercial products. For example, the disodium salt of 2-hydroxy-2-sulfonatoacetic acid is available under the name BLANCOLEN® HP from L. Brueggemann KG, Salzstrasse 131, 74076 Heilbronn, Germany, www.brueggemann.com.

[0068] The sulfonic acid derivatives are generally used in an amount of at least 0.0001% by weight, preferably at least 0.001% by weight, more preferably at least 0.025% by weight, such as at least 0.05% by weight or at least 0.1% by weight, and generally at most 3% by weight, preferably at most 2% by weight, more preferably at most 0.5% by weight, such as at most 0.35% by weight or 0.2% by weight, in each case based on the total weight of the superabsorbent.

[0069] As with the sulfonic acid derivatives, it is optionally possible to add at least one phosphonic acid derivative in a known manner, in addition thereto, or by itself, to the superabsorbent or otherwise monomer mixture before or after drying, preferably before drying. Particularly preferred is the additive (1-hydroxyethane-1,1-diyl)bisphosphonic acid ("etidronic acid") or its salts, in particular the sodium, potassium, disodium, dipotassium, or sodium potassium salts. For example, phosphonic acid derivatives of this type are standard commercial products and are available under the Modosol® (formerly Cublen®) brand from Zschimmer & Schwarz Mohsdorf GmbH & Co KG, Chemnitztalstrasse 1, 09217 Burgstaedt, Germany.

[0070] The phosphonic acid derivatives are generally added in an amount of at least 0.01% by weight, preferably at least 0.1% by weight, more preferably at least 0.2% by weight, and generally at most 1.9% by weight, preferably at most 1.3% by weight, more preferably at most 0.6% by weight, in each case based on the total amount of anhydrous superabsorber.

[0071] The polymer gel resulting from the aqueous polymerization and optional subsequent neutralization is then preferably dried using a belt dryer until the residual moisture is preferably 0.5-15% by weight, more preferably 1-10% by weight, most preferably 2-8% by weight (see below for test methods for residual moisture or residual water). If the residual moisture is too high, the dried polymer gel will have a very low glass transition temperature Tg and may even be difficult to process. If the residual moisture is too low, the dried polymer gel will be very brittle and the subsequent pulverization step will result in an unnecessarily large amount of polymer particles with an excessively low particle size ("fines"). The solids content of the gel before drying is generally 25-90% by weight, preferably 30-80% by weight, more preferably 35-70% by weight, most preferably 40-60% by weight. However, it is also possible to dry using a fluidized bed dryer or a heatable mixer equipped with a mechanical mixing unit, e.g. a paddle dryer, or similar dryers equipped with mixing implements of different designs. Optionally, the dryer can be operated under nitrogen or another non-oxidizing inert gas, or at least under low oxygen partial pressure, to prevent oxidative yellowing processes. Typically, however, sufficient aeration and vapor removal will result in an acceptable product. In general, a minimum drying time is favorable with respect to color and product quality.

[0072] During drying, the residual monomer content in the polymer particles also decreases and the last traces of initiator disappear.

[0073] The dried polymer gel is then optionally and preferably ground and classified, in which case the equipment used for grinding may typically be a single or multiple roll mill, preferably a two or three stage roll mill, a pin mill, a hammer mill or a vibratory mill. The oversize gel lumps, often not yet dry on the inside, are elastomeric and pose problems in grinding and are preferably removed before grinding, which can be done in a simple manner by air sorting or with a sieve ("guard sieve" for the mill). With respect to the mill used, the mesh size of the sieve should be selected so as to result in the lowest level of crushing of the elastomeric particles of the oversize.

[0074] Excessively large and inappropriately finely ground superabsorbent particles are perceptible as coarse particles in their main use in hygiene products, such as diapers, and they also reduce the average initial swelling rate of the superabsorbent. Both are undesirable. Therefore, advantageously, the coarse polymer particles are separated from the product. This is done by conventional classification methods, such as air sorting or sieving through sieves with a mesh size of at most 1000 μm, preferably at most 900 μm, more preferably at most 850 μm, most preferably at most 800 μm. For example, sieves with a mesh size of 700 μm, 650 μm, or 600 μm are used. The removed coarse polymer particles ("sieve overages") are returned to the grinding and sieving cycle or further processed separately to optimize costs.

[0075] Polymer particles with too small particle size reduce the permeability (SFC). Therefore, advantageously, this classification also removes fine polymer particles. If sieving is performed, this can be conveniently performed through a sieve with a mesh size of at most 300 μm, preferably at most 200 μm, more preferably at most 150 μm, most preferably at most 100 μm. The removed fine polymer particles ("undersieve" or "fines") can be optionally returned to the monomer stream, the polymerized gel, or the fully polymerized gel before drying the gel to optimize costs.

[0076] The average particle size of the polymer particles taken as the product fraction is generally at least 200 μm, preferably at least 250 μm, more preferably at least 300 μm, and generally at most 600 μm, more preferably at most 500 μm. The proportion of particles with a particle size of at least 150 μm is generally at least 90% by weight, more preferably at least 95% by weight, most preferably at least 98% by weight. The proportion of particles with a particle size of at most 850 μm is generally at least 90% by weight, more preferably at least 95% by weight, most preferably at least 98% by weight.

[0077] In some other known manufacturing methods for superabsorbents, especially in the case of suspension, spray or drop polymerization, the particle size distribution is defined by the selection of process parameters. These methods directly produce granular superabsorbents of the desired particle size, so that grinding and sieving steps may often be unnecessary. In some methods (especially in the case of spray or drop polymerization), a dedicated drying step may also often be unnecessary.

[0078] The polymer thus prepared has the properties of a superabsorbent and is included in the term "superabsorbent". Its CRC is typically relatively high, but its AUL or SFC is relatively low. This type of surface non-postcrosslinked superabsorbent is often called "base polymer" to distinguish it from the surface postcrosslinked superabsorbent produced from it.

[0079] If no surface postcrosslinking is performed or the X-ray amorphous aluminum hydroxide is added before surface postcrosslinking, it is added to this base polymer as described above.

[0080] The base polymer is optionally surface postcrosslinked. Surface postcrosslinkers for superabsorbents and methods of surface postcrosslinking of superabsorbents are well known. Suitable postcrosslinkers are compounds that contain groups capable of forming bonds with at least two functional groups of superabsorbent particles. In the case of acrylic acid / sodium acrylate-based superabsorbents, which are widely available on the market, suitable surface postcrosslinkers are compounds that contain groups capable of forming bonds with at least two carboxylate groups. Rather than "surface postcrosslinker" or "surface postcrosslinking", simply "postcrosslinker" or "postcrosslinking" is often used.

[0081] Preferred surface postcrosslinkers are di- or triglycidyl compounds, such as glycidyl ethers, for example ethylene glycol diglycidyl ether, and glycerol di- or triglycidyl ether.

[0082] Preferred surface postcrosslinkers are also 2-oxazolidones, such as 2-oxazolidones and N-(2-hydroxyethyl)-2-oxazolidones, N-methyl-2-oxazolidones, N-acyl-2-oxazolidones, such as N-acetyl-2-oxazolidones, 2-oxotetrahydro-1,3-oxazines, bicyclic amide acetals, such as 5-methyl-1-aza-4,6-dioxabicyclo[3.3.0]octane, 1-aza-4,6-dioxabicyclo[3.3.0]octane, and 5-isopropyl-1-aza-4,6-dioxabicyclo[3.3.0]octane, bis-2-oxazolidones, and poly-2-oxazolidones. Among these, 2-oxazolidone, N-methyl-2-oxazolidone, N-(2-hydroxyethyl)-2-oxazolidone, and N-hydroxypropyl-2-oxazolidone are particularly preferred.

[0083] More preferred post-crosslinking agents are propane-1,3-diol, pentane-1,5-diol, hexane-1,6-diol, and heptane-1,7-diol, butane-1,3-diol, octane-1,8-diol, nonane-1,9-diol, and decane-1,10-diol. Among these, those that are water-soluble at 23°C to the extent of at least 30% by weight, preferably at least 40% by weight, more preferably at least 50% by weight, and most preferably at least 60% by weight, are particularly preferred, such as propane-1,3-diol and heptane-1,7-diol. Those that are liquid at 25°C are even more preferred.

[0084] Further preferred post-crosslinking agents are butane-1,2,3-triol, butane-1,2,4-triol, glycerol, trimethylolpropane, trimethylolethane, pentaerythritol, 1-3 (per molecule) ethoxylated glycerol, trimethylolethane, or trimethylolpropane, and 1-3 (per molecule) propoxylated glycerol, trimethylolethane, or trimethylolpropane. In addition, doubly ethoxylated or propoxylated neopentyl glycol is preferred. Doubly and doubly ethoxylated glycerol, neopentyl glycol, 2-methylpropane-1,3-diol, and trimethylolpropane are particularly preferred. Of these, particular preference is given to those having a viscosity at 23° C. of less than 3000 mPas, preferably less than 1500 mPas, more preferably less than 1000 mPas, especially preferably less than 500 mPas, very especially preferably less than 300 mPas.

[0085] More preferred postcrosslinkers are ethylene carbonate and propylene carbonate.

[0086] A more preferred post-crosslinking agent is 2,2'-bis(2-oxazoline).

[0087] Likewise preferred postcrosslinkers are oxetanes, especially 3-ethyloxetane-3-methanol, or 3,3'-[oxybis(methylene)]bis[(3-ethyl)oxetane].

[0088] These preferred postcrosslinkers minimize side reactions and subsequent reactions that lead to volatile and therefore malodorous compounds, and therefore superabsorbents made with the preferred postcrosslinkers are odor-neutral even in wet conditions.

[0089] It is possible to use separate postcrosslinkers or any desired mixtures of different postcrosslinkers.

[0090] The postcrosslinker is generally used in an amount of at least 0.001% by weight, preferably at least 0.02% by weight, more preferably at least 0.05% by weight, and at most 2% by weight, preferably at most 1% by weight, more preferably at most 0.3% by weight, for example at most 0.15% by weight, or at most 0.095% by weight, in each case based on the mass of the base polymer (e.g. the sieve fraction) with which it is contacted.

[0091] Postcrosslinking is typically carried out in such a way that a solution of postcrosslinker is sprayed onto dried base polymer particles. After spray application, the polymer particles coated with postcrosslinker are dried by heat, and postcrosslinking reaction can be carried out either before or during drying. If a surface postcrosslinker having a polymerizable group is used, surface postcrosslinking can also be carried out using free radical induced polymerization of such groups using common free radical formers, or else using high energy radiation, for example UV light. This can be carried out in parallel with or instead of using a postcrosslinker that forms a covalent or ionic bond to the functional groups on the surface of the base polymer particles.

[0092] The spray application of the postcrosslinker solution is preferably carried out with a moving mixing device, such as a mixer with a screw mixer, a disk mixer, a paddle mixer, or a shovel mixer, or with a mixer with other mixing devices. However, vertical mixers are particularly preferred. It is also possible to spray the postcrosslinker solution in a fluidized bed. Suitable mixers are available, for example, as Pflugschar® (plowshare) mixers from Gebr.Loedige Maschinenbau GmbH, Elsener-Strasse 7-9, 33102 Paderborn, Germany, or as Schugi® Flexomix® mixers, Vrieco-Nauta® mixers, or Turbulizer® mixers from Hosokawa Micron BV, Gildenstraat 26, 7000 AB Doetinchem, Netherlands.

[0093] The usable spray nozzles are not subject to any restrictions. Suitable nozzles and atomization systems are described, for example, in Zerstaeuben von Fluessigkeiten [Atomization of Liquids], Expert-Verlag, Vol. 660, Reihe Kontakt & Studium, Thomas Richter (2004), and Zerstaeubungstechnik [Atomization Technology], Springer-Verlag, VDI-Reihe, Guenter Wozniak (2002). It is possible to use monodisperse and polydisperse spray systems. Among the polydisperse systems, single-phase pressure nozzles (jet-forming or lamellar-forming), rotary atomizers, two-phase atomizers, ultrasonic atomizers, and impingement nozzles are suitable. In the case of two-phase atomizers, the liquid phase may be mixed with the gas phase, either internally or externally. The spray profile of the nozzle is not important and can assume any desired form, for example a spray profile of a circular jet, a horizontal jet, a wide-angle round jet, or an annular ring. When a two-phase atomizer is used, it is advantageous to use a non-oxidizing gas, nitrogen, argon or carbon dioxide being particularly preferred. The liquid to be atomized can be fed to such a nozzle under pressure. Atomization of the liquid to be atomized can be achieved by expanding it in the nozzle bore when a specific minimum velocity is reached. In addition, it is also possible to use one-phase nozzles for inventive purposes, such as slit nozzles or swirl chambers (full cone nozzles) (e.g. from Duesen-Schlick GmbH, Germany or Spraying Systems Germany GmbH, Germany). Such nozzles are also described in EP 0 534 228 A1 and EP 1 191 051 A2.

[0094] Postcrosslinker is typically used in the form of aqueous solution.When water is used exclusively as solvent, surfactant or deagglomeration assistant is advantageously added to postcrosslinker solution or actually to base polymer.This improves wetting and reduces the tendency to form lumps.

[0095] Anionic, cationic, nonionic and amphoteric surfactants are all suitable as deagglomerating aids, but for skin compatibility reasons nonionic and amphoteric surfactants are preferred. The surfactants may also contain nitrogen. For example, sorbitan monoesters, such as sorbitan monococoate and sorbitan monolaurate, or their ethoxylated variants, such as Polysorbat 20®, are added. Further suitable deagglomerating aids are the ethoxylated and alkoxylated derivatives of 2-propylheptanol, which are sold under the Lutensol XL® and Lutensol XP® brands (BASF SE, Carl-Bosch-Strasse 38, 67056 Ludwigshafen, Germany).

[0096] The deagglomerating aid may be metered in separately or added to the postcrosslinker solution. It is preferred to simply add the deagglomerating aid to the postcrosslinker solution.

[0097] The amount of deflocculating aid used is, for example, 0% to 0.1% by weight, preferably 0% to 0.01% by weight, more preferably 0% to 0.002% by weight, based on the base polymer. The deflocculating aid is preferably metered in such that the surface tension of the aqueous extract of the swollen base polymer and / or the swollen post-crosslinked water-absorbing polymer at 23° C. is at least 0.060 N / m, preferably at least 0.062 N / m, more preferably at least 0.065 N / m, and advantageously at most 0.072 N / m.

[0098] The aqueous post-crosslinker solution also contains a co-solvent as well as at least one post-crosslinker. The content of the non-aqueous solvent or the total amount of the solvent can be used to adjust the penetration depth of the post-crosslinker into the polymer particles. Industrially, co-solvents that are readily available include C1-C6 alcohols, such as methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, or 2-methyl-1-propanol; 2 -C 5 Diols, such as ethylene glycol, 1,2-propylene glycol, or butane-1,4-diol, ketones, such as acetone, or carboxylic acid esters, such as ethyl acetate. The disadvantage of some of these cosolvents is that they have a typical intrinsic odor.

[0099] Cosolvent itself is ideally not a post-crosslinker under reaction conditions.However, in border cases and depending on the residence time and temperature at which cosolvent partially contributes to crosslinking, cosolvent may also partially contribute to crosslinking.This is especially the case when post-crosslinker is relatively slow to react and therefore can also constitute its own cosolvent, for example when cyclic carbonates, diols or polyols are used.Such post-crosslinker can also be used in the function of cosolvent when mixed with more reactive post-crosslinker, because then the actual post-crosslinking reaction can be carried out at lower temperature and / or shorter residence time than in the absence of more reactive crosslinker.Cosolvent must not be toxic, since it is used in relatively large amounts and some of it remains in the product.

[0100] In the method of the present invention, the above-mentioned diols, polyols, and also cyclic carbonates are also suitable as cosolvents.They fulfill this function in the presence of a relatively highly reactive postcrosslinker and / or di- or triglycidyl compounds.However, the preferred cosolvents in the method of the present invention are the above-mentioned diols, especially when the reaction of hydroxyl groups is sterically hindered by adjacent groups.Such diols are also suitable in principle as postcrosslinkers, but this requires significantly higher reaction temperatures or sometimes higher amounts to be used than in the case of sterically unhindered diols.

[0101] Particularly preferred combinations of low-reactivity postcrosslinkers as cosolvents and reactive postcrosslinkers are the combinations of the mentioned polyhydric alcohols, diols and polyols with the specified amide acetals or carbamates.For example, suitable combinations are 2-oxazolidone / propane-1,2-diol and N-(2-hydroxyethyl)-2-oxazolidone / propane-1,2-diol, and ethylene glycol diglycidyl ether / propane-1,2-diol. Particularly highly preferred combinations are 2-oxazolidone / propane-1,3-diol and N-(2-hydroxyethyl)-2-oxazolidone / propane-1,3-diol.Further preferred combinations are ethylene glycol diglycidyl ether, or glyceryl di- or triglycidyl ether, in combination with the following solvents, cosolvents or cocrosslinkers: isopropanol, propane-1,3-diol, 1,2-propylene glycol, or mixtures thereof. Further preferred combinations are 2-oxazolidone or (2-hydroxyethyl)-2-oxazolidone in the following solvents, co-solvents, or co-crosslinkers: isopropanol, propane-1,3-diol, 1,2-propylene glycol, ethylene carbonate, propylene carbonate, or mixtures thereof.

[0102] In most cases, the concentration of the cosolvent in the aqueous postcrosslinker solution is 15-50% by weight, preferably 15-40% by weight, more preferably 20-35% by weight, based on the postcrosslinker solution. In the case of cosolvents which have only limited miscibility with water, the aqueous postcrosslinker solution will advantageously be adjusted, possibly by reducing the concentration of the cosolvent, so that only one phase is present.

[0103] In a preferred embodiment, no co-solvent is used, and the postcrosslinker is then employed only as an aqueous solution, optionally with the addition of a deagglomerating aid.

[0104] The concentration of the at least one post-crosslinker in the aqueous post-crosslinker solution is typically 1 to 20% by weight, preferably 1.5 to 10% by weight, more preferably 2 to 5% by weight, based on the post-crosslinker solution.

[0105] The total amount of post-crosslinker solution is typically 0.3 to 15% by weight, preferably 2 to 6% by weight, based on the base polymer.

[0106] The actual surface postcrosslinking by reacting the surface postcrosslinker with the functional group on the surface of the base polymer particle is usually carried out by heating the base polymer wetted with the surface postcrosslinker solution, which is typically called "drying" (but should not be confused with the drying described above of the polymer gel from polymerization, which typically requires a lot of liquid to be removed). Drying can be carried out in the mixer itself by heating the jacket, using a heat exchange surface, or by blowing in warm gas; simultaneous mixing of the superabsorbent with the surface postcrosslinker and drying can be carried out, for example, in a fluidized bed dryer. However, drying is usually carried out in a downstream dryer, such as a tray dryer, a rotary tube oven, a paddle or disk dryer, or a heated screw. For example, suitable dryers are available as Solidair® or Torusdisc® dryers from Bepex International LLC, 333 NETaft Street, Minneapolis, MN 55413, USA, or as paddle or shovel dryers, otherwise fluidized bed dryers, from Nara Machinery Co., Ltd., European office, Europaallee 46, 50226 Frechen, Germany.

[0107] The polymer particles can be heated by contact surfaces in the downstream dryer for drying and carrying out the surface postcrosslinking, or by supplying warm inert gas, or by mixing with steam of one or more inert gases or by steam alone. When heat is supplied by contact surfaces, it is possible to carry out the reaction under inert gas at a slightly or completely reduced pressure. When steam is used for direct heating of the polymer particles, it is advisable to operate the dryer under normal or elevated pressure according to the invention. In this case, it may be sensible to divide the postcrosslinking step into a heating step with steam and a reaction step under inert gas but without steam. This can be achieved in one or more devices. According to the invention, the polymer particles can be heated initially with steam to the same extent as in the postcrosslinking mixer initially. The base polymer used may still have a temperature of 10-120°C from the preceding processing step, and the postcrosslinker solution may have a temperature of 0-70°C. In particular, the postcrosslinker solution can be heated to reduce the viscosity.

[0108] Preferred drying temperatures are in the range of 100-250° C., preferably 120-220° C., more preferably 130-210° C., most preferably 150-200° C. Preferred residence times at this temperature in the reaction mixer or dryer are preferably at least 10 minutes, more preferably at least 20 minutes, most preferably at least 30 minutes, typically at most 60 minutes. Typically, drying is carried out such that the superabsorbent generally has a residual moisture of at least 0.1% by weight, preferably at least 0.2% by weight, at least 0.5% by weight, and at most 15% by weight, preferably at most 10% by weight, more preferably at most 8% by weight.

[0109] Postcrosslinking can take place under standard atmospheric conditions. "Standard atmospheric conditions" means that no technical precautions are taken to reduce the partial pressure of oxidizing gases, such as the partial pressure of atmospheric oxygen, in the equipment in which the postcrosslinking reaction mainly takes place ("postcrosslinking reactor", typically a dryer). However, it is preferred to carry out the postcrosslinking reaction under reduced partial pressure of oxidizing gases. Oxidizing gases are substances that have a vapor pressure of at least 1013 mbar at 23°C and act as oxidizing agents in combustion processes, such as oxygen, nitrogen oxides and nitrogen dioxide, especially oxygen. The partial pressure of the oxidizing gas is preferably less than 140 mbar, preferably less than 100 mbar, more preferably less than 50 mbar, most preferably less than 10 mbar. If the thermal postcrosslinking is carried out at ambient pressure, i.e. a total pressure of about 1013 mbar, the total partial pressure of the oxidizing gases is determined by their volume fraction. The fraction of oxidizing gases is preferably less than 14% by volume, preferably less than 10% by volume, more preferably less than 5% by volume, most preferably less than 1% by volume.

[0110] Postcrosslinking can be carried out under reduced pressure, i.e. at a total pressure of less than 1013 mbar. The total pressure is typically less than 670 mbar, preferably less than 480 mbar, more preferably less than 300 mbar, most preferably less than 200 mbar. If drying and postcrosslinking are carried out under air with an oxygen content of 20.8% by volume, the oxygen partial pressures corresponding to the above total pressures are 139 mbar (670 mbar), 100 mbar (480 mbar), 62 mbar (300 mbar), and 42 mbar (200 mbar), the respective total pressures being in brackets. Another way to reduce the partial pressure of oxidizing gases is the introduction of non-oxidizing gases, especially inert gases, into the device used for postcrosslinking. Suitable inert gases are substances that are present in gas form in the postcrosslinking dryer at the postcrosslinking temperature and given pressure and that do not have an oxidizing effect on the constituents of the dried polymer particles under these conditions, such as nitrogen, carbon dioxide, argon, steam, nitrogen being preferred. The amount of inert gas is generally between 0.0001 and 10 m, based on 1 kg of superabsorbent. 3 , preferably 0.001 to 5 m 3 , more preferably 0.005 to 1 m3 , and most preferably 0.005 to 0.1 m 3 It is.

[0111] In the process of the present invention, the inert gas, if it does not contain steam, can be blown into the postcrosslinking dryer through a nozzle, but it is particularly preferred to add the inert gas to the polymer particle stream through a nozzle that is actually in the mixer or immediately upstream of the mixer by mixing the superabsorbent with the surface postcrosslinker.

[0112] It will be appreciated that co-solvent vapors removed from the dryer may be re-condensed outside the dryer and optionally reused.

[0113] One way of adding X-ray amorphous aluminum hydroxide during surface post-crosslinking is to add it to the equipment used for surface post-crosslinking reaction, when the contents are mixed in this equipment, and mix it during surface post-crosslinking reaction.Suitable equipment is, for example, the equipment described above for this purpose, except for the tray dryer.Preferably use paddle and shovel dryer for this purpose.

[0114] In addition to the organic postcrosslinkers mentioned, which form covalent bonds with the carboxyl groups in the superabsorbent before, during or after postcrosslinking, and in addition to the X-ray amorphous aluminum hydroxide, polyvalent metal ions are optionally applied to the surface of the superabsorbent of the invention, or instead of it, if surface postcrosslinking is not carried out with one of the organic postcrosslinkers mentioned.As already mentioned above, this application of polyvalent metal ions is in principle an (optionally additional) surface postcrosslinking by ionic non-covalent bonds, which in the context of the present invention is called "complexation" with said metal ions, in order to distinguish it from surface postcrosslinking by covalent bonds.

[0115] This application of polyvalent cations is typically carried out by spraying a solution of divalent or polyvalent cations, usually divalent, trivalent or tetravalent metal cations, but also polyvalent cations, such as vinylamine monomers, formally fully or partially formed polymers, such as partially or completely hydrolyzed polyvinylamides (so-called "polyvinylamines"), in which the amine groups are always present in a partially protonated form even at very high pH values ​​to give ammonium groups. Examples of divalent metal cations that can be used are, inter alia, the divalent cations of metals of groups 2 (especially Mg, Ca, Sr, Ba), 7 (especially Mn), 8 (especially Fe), 9 (especially Co), 10 (especially Ni), 11 (especially Cu) and 12 (especially Zn) of the periodic table of elements. Examples of usable trivalent metal cations are in particular the trivalent cations of metals from group 3 (especially Sc, Y, La, Ce), group 8 (especially Fe), group 11 (especially Au), group 13 (especially Al) and group 14 (especially Bi) of the periodic table of elements. Examples of usable tetravalent cations are in particular the tetravalent cations of metals from group 4 (especially Ti, Zr, Hf) and group 3 (especially Au), including the lanthanides of the periodic table of elements. The metal cations can be used either alone or in a mixture with each other. The use of trivalent metal cations is particularly preferred. The use of aluminum cations is very particularly preferred.

[0116] Among the metal cations mentioned, suitable metal salts are all those that have sufficient solubility in the solvent used. Particularly suitable metal salts are those with weakly complexing anions, such as chlorides, nitrates and sulfates, hydrogen sulfates, carbonates, hydrogen carbonates, nitrates, phosphates, hydrogen phosphates or dihydrogen phosphates. Salts of mono- and dicarboxylic acids, hydroxy acids, keto acids and amino acids or base salts are preferred. Preferred examples include acetates, propionates, tartrates, maleates, citrates, lactates, malates, succinates. Likewise, the use of hydroxides is preferred, provided that they are soluble. The use of 2-hydroxycarboxylic acid salts, such as citrates and lactates, is particularly preferred. Examples of particularly preferred metal salts are alkali metal and alkaline earth metal aluminates and their hydrates, such as sodium aluminate and its hydrates, alkali metal and alkaline earth metal lactates and citrates and their hydrates, aluminum acetate, aluminum propionate, aluminum citrate, and aluminum lactate.

[0117] The mentioned cations and salts can be used in pure form or as a mixture of different cations or salts. The salts of divalent and / or trivalent metal cations used may contain further secondary constituents, such as alkali metal salts of still unneutralized carboxylic acids and / or neutralized carboxylic acids. Preferred alkali metal salts are the alkali metal salts of sodium and potassium, as well as the alkali metal salts of ammonium. They are typically used in the form of aqueous solutions obtained by dissolving the solid salt in water or preferably directly as such, thereby avoiding any drying and purification steps. Advantageously, hydrates of the mentioned salts can also be used, which often dissolve more quickly in water than the anhydrous salts.

[0118] The amount of metal salt used is generally at least 0.001% by weight, preferably at least 0.01% by weight, more preferably at least 0.1% by weight, for example at least 0.4% by weight, and at most 5% by weight, preferably at most 2.5% by weight, more preferably at most 1% by weight, for example at most 0.7% by weight, in each case based on the mass of the base polymer.

[0119] The salt of the trivalent metal cation can be used in the form of a solution or suspension. The solvent used for the metal salt can be water, alcohol, DMF, DMSO, and mixtures of these components. Particularly preferred are water and water / alcohol mixtures, such as water / methanol, water / propane-1,2-diol, and water / propane-1,3-diol.

[0120] The treatment of the base polymer with the solution of divalent or polyvalent cation is carried out in the same manner as the treatment with the surface postcrosslinker, including the drying step. The surface postcrosslinker and the polyvalent cation can be sprayed in a combined solution or as separate solutions. The spray application of the metal salt solution to the superabsorbent particles can be carried out before or after the surface postcrosslinking. In a particularly preferred manner, the spray application of the metal salt solution is carried out in the same step together with the spray application of the crosslinker solution, in which case the two solutions are sprayed separately through two nozzles in succession or simultaneously, or the crosslinker solution and the metal salt solution can be sprayed together through one nozzle.

[0121] It is also possible to add all known further additives during the surface postcrosslinking of superabsorbents.Examples are basic salts of divalent metal cations, such as calcium or strontium, usually in the form of hydroxide, hydrogencarbonate, carbonate, acetate, propionate, citrate, gluconate, lactate, tartrate, malate, succinate, maleate and / or fumarate.Further examples are reducing compounds, such as hypophosphites, phosphonic acid derivatives, sulfinates or sulfites.

[0122] More preferably, apart from the addition of X-ray amorphous aluminium hydroxide, no further polyvalent metal ions are added.

[0123] If the drying step is carried out after the surface postcrosslinking and / or treatment with a complexing agent, it is advantageous, but not necessary, to cool the product after the drying step. The cooling can be carried out continuously or batchwise, for which the product is conveniently conveyed continuously to a cooler arranged downstream of the dryer. Any known device for removing heat from pulverulent solids can be used for this purpose, more particularly any device described above as a drying device, except that it is filled with cooling water, e.g. a cooling medium, rather than a heating medium, so that heat is not conducted to the superabsorbent through the walls, and depending on the structure, also through stirring elements or other heat exchange surfaces, but is instead removed from it. The use of a cooler through which the product is moved, i.e. a cooling mixer, e.g. a shovel cooler, a disk cooler or a paddle cooler, is preferred. The superabsorbent can also be cooled in a fluidized bed by injecting a cooling gas, e.g. cold air. The cooling conditions are adjusted to obtain the superabsorbent at the desired temperature for further processing. Typically, an average residence time in the cooler is set to generally at least 1 minute, preferably at least 3 minutes, more preferably at least 5 minutes, and at most 6 hours, preferably at most 2 hours, more preferably at most 1 hour, and the cooling performance is such that the temperature of the resulting product is generally at least 0°C, preferably at least 10°C, more preferably at least 20°C, and at most 100°C, preferably at most 80°C, more preferably at most 60°C.

[0124] Surface post-crosslinked superabsorbent is optionally ground and / or sieved in a conventional manner.Grinding is not typically required here, but removing the agglomerates or fines formed by sieving is usually adequate to establish the desired particle size distribution of the product.Agglomerates and fines are discarded, or preferably agglomerates after pulverization are recycled to the process at the appropriate time in a known manner.The particle size desired for surface post-crosslinked superabsorbent is the same as that for base polymer.

[0125] If the X-ray amorphous aluminum hydroxide is added after the surface post-crosslinking, this can be conveniently carried out in a downstream cooler, but can also be carried out in a dedicated mixing device. The X-ray amorphous aluminum hydroxide can in any case be added either before or after the sieving and grinding step that follows the surface post-crosslinking operation.

[0126] Optionally, the inventive superabsorbent produced by the inventive method comprises further additives, non-limiting examples being additives that provide stability against discoloration, reduce the tendency to caking or further increase the permeability. For this purpose, all known additives can be used in the inventive method in a known manner for each. Examples of known additives that provide stability against discoloration are the above-mentioned sulfonic acid or phosphonic acid derivatives, which can be applied after the inventive superabsorbent is produced rather than added during its production, or can also be applied as well as added during its production. Examples of known additives that reduce the tendency to caking or further increase the permeability of the superabsorbent are water-insoluble inorganic powders.

[0127] Usually, the X-ray amorphous aluminum hydroxide added according to the invention will also sufficiently reduce the caking tendency of the superabsorbent. If the amount added according to the invention is insufficient for this purpose, it can be increased beyond the above ranges to the extent that the desired reduction in caking tendency is achieved. This additional amount of X-ray amorphous aluminum hydroxide can also be added in a second portion, like other water-soluble inorganic powders. Typically, the additional amount of X-ray amorphous aluminum hydroxide is at least as much as other water-insoluble inorganic powders.

[0128] When further inorganic powders are added, more preferably, precipitated silicon dioxide or pyrogenically produced silicon dioxide and pyrogenically produced aluminum oxide are used. Pyrogenic silicon dioxide is available, for example, under the AEROSIL® brand, and pyrogenic aluminum oxide is available, for example, under the AEROXIDE® Alu brand, from Evonik Industries AG, Inorganic Materials, Rodenbacher Chaussee 4, 63457 Hanau-Wolfgang, Germany. Precipitation-produced silicon dioxide is available, for example, under the SIPERNAT® brand, from Evonik Industries AG, Inorganic Materials, Rodenbacher Chaussee 4, 63457 Hanau-Wolfgang, Germany. Water-insoluble inorganic powders can be hydrophobized by suitable surface treatment, and are often supplied by manufacturers in both hydrophobized and hydrophilic forms. In the context of the present invention, the use of hydrophilic water-insoluble inorganic powders is preferred.

[0129] Generally, the water-insoluble inorganic powder is added to the superabsorbent in an amount of at least 0.005% by weight, preferably at least 0.03% by weight, more preferably at least 0.05% by weight, and generally at most 6.0% by weight, preferably at most 1.0% by weight, more preferably at most 0.5% by weight, in each case based on the total weight of the anhydrous superabsorbent including the inorganic powder.

[0130] The superabsorbent can be mixed with optional additives by any known mixing method. If in solid form, they are incorporated by mixing the substances or as a suspension in a solvent or suspension medium, and if in dissolved or liquid form, they are optionally also incorporated in solution or liquid form. The additives are preferably incorporated into the superabsorbent by mixing as a powder or suspension, since homogeneous distribution is easier. This produces a physical mixture that can be separated in a simple manner by mechanical means, although this is not necessarily the case. The additives are quite likely to be more securely bound to the superabsorbent, for example in the form of a relatively tightly adhering surface layer or in the form of particles that are tightly adhered to the surface of the superabsorbent particles. The mixing of additives into known superabsorbents is also quite likely to be understood and sometimes referred to as "coating".

[0131] When a solution or suspension is used for coating, the solvent or suspension medium used is one that is chemically compatible with both the superabsorbent and the additive, i.e. does not undergo any undesired chemical reaction with them. Typically, water or an organic solvent, such as an alcohol or polyol, or a mixture thereof, is used. Examples of suitable solvents or suspension media are water, isopropanol / water, propane-1,3-diol / water, and propylene glycol / water, where the mixing weight ratio is preferably 20:80 to 40:60. When a suspension medium is used for the stabilizer or inorganic particulate solids used according to the invention, water is preferred. Surfactants can be added to the solution or suspension.

[0132] Optional additives, if they are not added to the monomer mixture or polymer gel, are generally mixed with the superabsorbent in exactly the same way as a solution or suspension containing the surface postcrosslinker and applied to the superabsorbent for surface postcrosslinking. The additives can be applied to the (for now) non-postcrosslinked superabsorbent ("base polymer") as a constituent of the solution or one of its components that is applied for surface postcrosslinking, i.e. the additives are added to the solution of the surface postcrosslinker or one of its components. The superabsorbent coated with the surface postcrosslinker and additives then undergoes further processing steps required for surface postcrosslinking, such as the thermally induced reaction of the surface postcrosslinker with the superabsorbent. This processing is relatively simple and economically feasible.

[0133] If the superabsorbent is subjected to a cooling step after surface postcrosslinking or complex formation, the optional additives can be conveniently mixed in the cooler. If the additives are applied as a solution or suspension, they can also be applied in the same mixing device to the already surface postcrosslinked superabsorbent, as described for the application of the surface postcrosslinker to the base polymer. Usually, but not necessarily, this is followed by heating again to dry the superabsorbent, similar to the surface postcrosslinking step. However, the temperature set in this drying operation is then generally at most 110°C, preferably at most 100°C, more preferably at most 90°C, in order to prevent undesired reactions of the additives. The temperature is adjusted so that the desired moisture of the superabsorbent is achieved, taking into account the residence time in the drying unit. It is entirely possible and convenient to add the additives separately or together with other conventional auxiliaries, such as dust binders, anticaking agents, or water to remoisten the superabsorbent. The temperature of the polymer particles in this case is between 0° C. and 190° C., preferably below 160° C., more preferably below 130° C., even more preferably below 100° C., and most preferably below 70° C. The polymer particles are optionally rapidly cooled after coating to a temperature below any decomposition temperature of the additive.

[0134] It is possible to optionally apply, at any processing stage of the preparation method, to the surface of the superabsorbent particles, whether postcrosslinked or not, in addition, all known coatings, such as film-forming polymers, thermoplastic polymers, dendrimers, polycationic polymers (e.g. polyvinylamine, polyethyleneimine or polyallylamine), or all water-soluble monovalent or polyvalent metal salts known to those skilled in the art, such as aluminum sulfate, sodium salts, potassium salts, zirconium salts or iron salts. Examples of useful alkali metal salts are sodium and potassium sulfate, as well as sodium and potassium lactate, sodium and potassium citrate and sodium and potassium sorbate. This allows for further effects, such as a reduction in the tendency of the final product or intermediate to solidify in certain processing steps of the production method, an improvement in the processing properties or an additional enhancement of the permeability (SFC). If the additives are used and sprayed in the form of a dispersion, they are preferably used in the form of an aqueous dispersion, and preferably applied with an anti-dusting agent to fix the additives to the surface of the superabsorbent. The anti-dusting agent is then added directly to the dispersion of the inorganic powdery additive or, optionally, it can also be added as a separate solution before, during or after the application of the inorganic powdery additive by spray application. In the post-crosslinking step, it is most preferred to spray-apply the post-crosslinker, the anti-dusting agent and the powdery inorganic additive simultaneously. However, in a further preferred method variant, the anti-dusting agent is added separately in the cooler, for example by spray application from above, below or the side. Particularly suitable anti-dusting agents, which can also serve to fix the powdery inorganic additive on the surface of the water-absorbing polymer particles, are polyethylene glycols with molecular weights of 400 to 20,000 g / mol, polyglycerols, 3-100 ethoxylated polyols, such as trimethylolpropane, glycerol, sorbitol and neopentyl glycol. Particularly suitable are 7-20 ethoxylated glycerol or trimethylolpropane, such as Polyol TP70® (Perstorp, Sweden). More particularly, the latter has the advantage of only slightly reducing the surface tension of the aqueous extract of the water-absorbing polymer particles.

[0135] Likewise, the superabsorbent of the present invention can be adjusted to the desired moisture content by adding water, which may be convenient to slightly swell the superabsorbent and then adjust it back to the desired moisture content by drying it.

[0136] All coatings, solids, additives and auxiliaries can be added in separate processing steps, but the most convenient way is usually to add them to the superabsorbent in the cooler, if not during mixing of the base polymer with the surface postcrosslinker, for example by spray application of a solution or adding in finely divided solid or liquid form.

[0137] The superabsorbents of the present invention generally have a centrifuge retention capacity (CRC, see below for test method) of at least 5 g / g, preferably at least 10 g / g, more preferably at least 20 g / g. Typically, it is up to 40 g / g for surface postcrosslinked superabsorbents, but is often higher for base polymers.

[0138] The superabsorbents of the present invention, when they are surface postcrosslinked, typically have a water absorption under load (AUL 0.9 psi, see below for test method) of at least 10 g / g, preferably at least 14 g / g, more preferably at least 18 g / g, most preferably at least 22 g / g, and typically no more than 30 g / g.

[0139] The present invention further provides a hygiene article, preferably an ultra-thin diaper, comprising a superabsorbent according to the invention, comprising an absorbent layer consisting of 50 to 100% by weight, preferably 60 to 100% by weight, more preferably 70 to 100% by weight, especially preferably 80 to 100% by weight, very especially preferably 90 to 100% by weight of the superabsorbent according to the invention, of course not including the packaging of the absorbent layer.

[0140] Particularly and very advantageously, the superabsorbents of the invention are also suitable for producing laminates and composite structures, such as those described, for example, in US Patent Application Publication No. 2003 / 0181115 and US Patent Application Publication No. 2004 / 0019342. In addition to the hot melt adhesives described in both documents for producing such novel absorbent structures, and in particular the fibers composed of hot melt adhesives to which superabsorbent particles are bonded, as described in US Patent Application Publication No. 2003 / 0181115, the superabsorbents of the invention are also suitable for producing completely similar structures, for example using UV-crosslinkable hot melt adhesives sold under the name AC-Resin® (BASF SE, Ludwigshafen, Germany). These UV-crosslinkable hot melt adhesives have the advantage that they are already processable at 120-140° C. and therefore have a better compatibility with many thermoplastic substrates. A further notable advantage is that the UV-crosslinkable hot melt adhesives are extremely benign in toxicological terms and do not cause any evaporation in hygiene articles. A very big advantage of the superabsorbents of the present invention is the property of UV-crosslinkable hot melt adhesives that they do not tend to yellow during processing and crosslinking. This is particularly advantageous when it is intended to produce very thin or partially transparent hygiene articles. Therefore, the combination of the superabsorbents of the present invention with UV-crosslinkable hot melt adhesives is particularly advantageous. Suitable UV-crosslinkable hot melt adhesives are described, for example, in EP-A-0377199 (A2), EP-A-0445641 (A1), US Patent No. 5,026,806, EP-A-0655465 (A1) and EP-A-0377191 (A2).

[0141] The superabsorbents of the invention can also be used in other sectors of industry where fluids, especially water or aqueous solutions, are absorbed. These sectors are, for example, storage, packaging, transport (as a component of packaging materials for the transport of water- or moisture-sensitive items, such as flowers, and also as protection against mechanical influences), animal health (in cat litter), food packaging (transport of fish, fresh meat, absorption of water, blood in the packaging of fresh fish or meat), medicine (wound dressings, absorbent materials for burn dressings or for other exuding wounds), cosmetics (carrier materials for pharmaceutical chemicals and medicines, rheumatism dressings, ultrasound gels, cooling gels, cosmetic thickeners, sunscreens), thickeners for oil / water or water / oil emulsions, textiles (textiles for evaporative cooling, shoe insoles, moisture regulation in e.g. protective clothing, gloves, headbands), chemical engineering applications (catalysts for organic reactions, immobilization of large functional molecules e.g. enzymes, adhesives in flocculation, heat storage agents, filter aids, hydrophilic components in polymer laminates, dispersants, liquefiers), as auxiliary in powder injection moulding in the building and construction industry (loam-based undercoats for installation in water-rich renders, vibration dampening medium, aid in tunnel excavation in water-rich grounds, as cable sheaths), water treatment, waste treatment, moisture removal (de-icing equipment, reusable sandbags), cleaning, the agrochemical industry (irrigation, retention of meltwater and dew deposits, compost additives, protection of forests from fungal / insect infestations, delayed release of active ingredients to plants), for firefighting or fire protection, co-extrusion agents in thermoplastic polymers (e.g. to make multi-layer films hydrophilic), production of membranes and thermoplastic mouldings capable of absorbing water (e.g. membranes to store rain and dew for agriculture, membranes containing superabsorbents to maintain the freshness of fruits and vegetables packaged in moist membranes, e.g. superabsorbent-polystyrene co-extrusions for packaging food products such as meat, fish, poultry, fruits and vegetables) or carrier material in active ingredient formulations (pharmaceuticals, crop protection).

[0142] The articles of the present invention for absorbing fluids differ from known examples in that they contain the superabsorbent of the present invention.

[0143] It has also been found a method for producing an article for absorbing fluids, in particular a hygiene article, which comprises the step of using at least one superabsorbent according to the invention in the production of said article. In addition, methods for producing such articles using superabsorbents are known.

[0144] Test Method The superabsorbents are tested according to the test methods described below.

[0145] The standard test method described below and referred to as "NWSP" is described in: "Nonwovens Standards Procedures", 2015 edition, jointly published by EDANA (European Disposables and Nonwovens Association, Avenue Herrmann Debroux 46, 1160 Brussels, Belgium, www.edana.org) and INDA (Association of the Nonwoven Fabrics Industry, 1100 Crescent Green, Suite 115, Cary, North Carolina 27518, USA, www.inda.org). This publication is available from EDANA and INDA.

[0146] All measurements described below are carried out at an ambient temperature of 23±2° C. and a relative air humidity of 50±10%, unless otherwise indicated. The superabsorbent particles are thoroughly mixed before the measurements, unless otherwise indicated.

[0147] Centrifugal holding capacity (CRC) The centrifuge retention capacity of a superabsorbent is determined by the method described in US Patent Application Publication No. 2007 / 0135785(A1), paragraphs

[0153] to

[0157] .

[0148] Absorbency under load of 0.9 psi (AUL 0.9 psi) The absorbency under a load of 6205 Pa (0.9 psi) (AUL 0.9 psi) of a superabsorbent is determined by the method described in U.S. Patent Application Publication No. 2014 / 0306156(A1), paragraphs

[0124] to

[0143] .

[0149] Absorbency under load of 0.3 psi (AUL 0.3 psi) The absorbency under a load of 2068 Pa (0.3 psi) (AUL 0.3 psi) of a superabsorbent is determined by standard test method No. NWSP 242.0 R2(15) "Gravimetric Determination of Absorption Against Pressure", but a pressure of 2068 Pa is set rather than 4826 Pa (49 g / cm 2 rather than 21g / cm 2 (corresponding to 100 g / kg) weight (see point 6.5 of the method description).

[0150] Volume Absorption Under Load (VAUL) The volumetric absorbency under load of a superabsorbent is determined by the method described in U.S. Patent Application Publication No. 2015 / 0299404(A1), paragraphs

[0386] to

[0398] . In Table 1, τ values ​​determined at a pressure of 2068 Pa (0.3 psi) are reported.

[0151] Moisture content of superabsorbents (residual moisture, water) The moisture content of superabsorbents is determined by standard test method No. NWSP 230.0 R2(15) "Estimation of the Moisture Content as Weight Loss Upon Heating".

[0152] Particle Size Distribution The particle size distribution of superabsorbents is determined by standard test method No. NWSP 220.0 R2(15) "Determination of Polyacrylate Superabsorbent Powders and Particle Size Distribution-Sieve Fractionation".

[0153] extract Extractables in superabsorbents are determined by standard test method No. NWSP 270.0 R2(15) "Determination of Extractable Polymer Content by Potentiometric Titration".

[0154] Permeability (SFC, "Saline Flow Conductivity") The permeability of the swollen gel layer formed by the superabsorbent as a result of liquid absorption is determined as the gel layer permeability of the swollen gel layer of the superabsorbent particles under a pressure of 0.3 psi (2068 Pa) as described in EP 0 640 330 A1, the device described on page 19 and in FIG. 8 of said patent application being modified in such a way that no glass frit (40) is used and the plunger (39) is made of the same polymeric material as the cylinder (37) and contains 21 equally sized bores uniformly distributed over the entire contact surface. The measurement procedure and evaluation remain unchanged from EP 0 640 330 A1. The flow rate is detected automatically.

[0155] The permeability (SFC) is calculated as follows: SFC[cm 3 s / g]=(Fg(t=0)×L0) / (d×A×WP) where Fg(t=0) is the flow rate of the NaCl solution in g / s, which was obtained using linear regression analysis of the Fg(t) data to determine the flow rate by extrapolation to t=0, L0 is the gel layer thickness in cm, and d is the gel layer thickness in g / cm 3 is the density of the NaCl solution in units of cm 2 is the area of ​​the gel layer in units, and WP is in dyn / cm 2 (where is the hydrostatic pressure on the gel layer per unit).

[0156] Permeability (GBP, "Gel Bed Permeability") Gel bed permeability is measured by the method of published patent application US Patent Application Publication No. 2005 / 0256757(A1), paragraphs

[0061] to

[0075] . EXAMPLES

[0157] The base polymers used in examples 1 to 7 were prepared by polymerizing an aqueous monomer solution containing sodium acrylate and acrylic acid in a concentration of 41% by weight (sodium acrylate and acrylic acid based on the total amount) (corresponding to a neutralization level of 71 mol% of acrylic acid), and 0.75% by weight (based on non-neutralized acrylic acid) of polyethylene glycol-4000 (polyethylene glycol with an average molar mass of 4000 g / mol), and 0.46% by weight (based on non-neutralized acrylic acid) of triacrylate of triethoxylated glycerol. The initiator system used (in each case based on non-neutralized acrylic acid) was 0.184% by weight of sodium persulfate, 0.0007% by weight of hydrogen peroxide, and 0.0026% by weight of ascorbic acid. The polymerization was carried out in a kneader. For better drying, the gel obtained was extruded, then dried and crushed, from which sieve cuts of 150 to 710 μm were obtained. The base polymer thus prepared had a CRC of 36.5 g / g, an AUL 0.3 psi of 14.6 g / g, and contained 13.0 wt % extractables. The particle size distribution obtained using sieve analysis was as follows: >850μm <0.1wt% 600~850μm 10.6% by weight 300~600μm 70.8wt% 100~300μm 18.0% by weight <100μm <0.5wt%

[0158] Base polymers of this type are standard and commercially available, for example, from BASF SE, Ludwigshafen, Germany.

[0159] The mixer used in the examples was a 5 L Pflugschar® 5R-MK ploughshare mixer, model VT 5R-MK, equipped with a heating jacket, from Gebr.Loedige Maschinenbau GmbH, Elsener Strasse 7-9, 33102 Paderborn, Germany. To measure the temperature of the product in the mixer, a thermocouple was introduced into an opening provided for that purpose in the mixer, with its tip located away from the heated inner wall of the mixer and in the product, but to the extent that it could not be influenced by the mixing equipment. For the additional aluminum hydroxide of Examples 1 to 6, the same mixer was used, but without a heating jacket and a thermocouple.

[0160] The X-ray amorphous aluminum hydroxide used in the examples was aluminum hydroxide dry gel, catalogue number 511066100, batch number 3048632, from Dr. Paul Lohmann GmbH KG, Hauptstrasse 2, 31860 Emmerthal, Germany. Scanning electron microscopy showed that the powder was in the form of spherical particles with diameters in the region of 20-25 μm, with some small spheres with diameters in the region of 5-10 μm. The X-ray diffractogram (measured on a D8 Advance Series 2 diffractometer from Bruker Corporation, 40 Manning Road, Billerica, MA 01821, USA, equipped with a multiple specimen changer, Cu anode, divergence slit 0.1° with ASS, and Lynx-Eye, 3° aperture) did not measure any diffraction lines, which indicates that the size of the primary crystallites is clearly smaller than 2 nm.

[0161] [Example 1 (Comparison)] 1.2 kg of superabsorbent base polymer was initially charged into the mixer. At 23° C. and a shaft speed of 200 rpm, a nitrogen-driven two-phase spray nozzle was used to spray a solution of 0.08% by weight of ethylene glycol diglycidyl ether, 2.5% by weight of propane-1,2-diol, and 3% by weight of water, in each case based on the base polymer. The shaft speed was then reduced to 60 rpm and the product temperature was increased to 130° C. and maintained thereafter for 30 minutes.

[0162] Immediately after (product temperature at that time was about 100° C.), the resulting superabsorbent was mixed with 0.1% by weight of X-ray amorphous aluminum hydroxide based on the superabsorbent in a further mixer at a shaft speed of 200 revolutions per minute (mixing time about 1 min). After the aluminum hydroxide was mixed, 4.0% by weight of water based on the superabsorbent was also sprayed (at a rate of 38 g / min) and mixed using a nitrogen-driven two-phase nozzle. Sieve pieces of 150 to 710 μm were then obtained.

[0163] The superabsorbent thus obtained was analyzed and the measurements obtained are reported in Table 1.

[0164] [Example 2 (Comparison)] Example 1 was repeated, except that the total amount of water was added in two portions of 2.0% by weight, with the second portion being added after mixing of the first portion (about 15 seconds of mixing time). Samples were taken after each water addition step. The measurements obtained are reported in Table 1.

[0165] [Example 3] Example 1 was repeated, except that the total amount of water was added in four portions of 1.0 wt.%, each portion being added after mixing of the previous portion (approximately 15 seconds of mixing time). The measurements obtained are reported in Table 1.

[0166] Evaluation of Examples 1-3 A comparison between Examples 1-3 shows that adding the same amount of water in at least three separate additions rather than all at once improves GBP without significantly affecting CRC and AUL.

[0167] [Example 4] Example 3 was repeated except that the amount of aluminum hydroxide was increased to 0.3 wt %.

[0168] [Example 5] Example 3 was repeated except that the amount of aluminum hydroxide was increased to 0.5 wt %.

[0169] Evaluation of Examples 3-5 A comparison between Examples 3-5 shows the effect of the amount of aluminum hydroxide on the GBP. For the superabsorbent and water addition method of this example, aluminum hydroxide above 0.3 wt % does not further increase the GBP.

[0170] [Example 6 (Comparison)] Example 3 was repeated except that the amount of aluminum hydroxide was increased to 0.3 wt %.

[0171] [Example 7 (Comparison)] Example 3 was repeated except that the amount of aluminum hydroxide was increased to 0.3 wt %.

[0172] Evaluation of Examples 6-7 Examples 6 and 7, compared to Examples 4 and 5, respectively, show that by adding the same amount of water in at least three instalments rather than all at once, GBP is improved at higher aluminum hydroxide levels without significantly affecting CRC and AUL.

[0173] [Example 8] 1.2 kg of a standard commercially available surface postcrosslinked superabsorbent polymer was charged into the mixer.

[0174] At 23°C and a shaft speed of 200 rpm, 0.3% by weight of x-ray amorphous aluminum hydroxide based on the superabsorbent was added to the superabsorbent and mixed for 15 seconds. Then, using a nitrogen-driven two-phase nozzle, four portions of water, each 1.0% by weight based on the superabsorbent, were also sprayed (at a rate of 38 g / min) and mixed. The mixing time after the addition of each portion of water except the last was 15 seconds. After the last portion, the superabsorbent was mixed for 300 seconds. After each water addition and mixing, a sample was taken and a sieve fraction of 150-710 μm was obtained.

[0175] The samples thus obtained were analyzed and the measurements obtained are reported in Table 2.

[0176] [Example 9] Example 8 was repeated except that the mixing time after addition of each portion of water except the last was 60 seconds.

[0177] [Example 10] Example 8 was repeated except that the mixing time after addition of each portion of water except the last was 300 seconds.

[0178] [Example 11] Example 8 was repeated, except that the mixing time after addition of each portion of water except the last was 600 seconds.

[0179] Evaluation of Examples 8-11 Examples 8-11 show that extending the time between addition of each portion of water does not further improve or decrease GBP.

[0180] [Table 1]

[0181] [Table 2]

Claims

1. 1. A method for producing a superabsorbent, comprising the steps of: a) at least one ethylenically unsaturated monomer having an acidic group, optionally at least partially in salt form; b) at least one crosslinking agent; c) at least one initiator; d) optionally one or more ethylenically unsaturated monomers copolymerizable with the monomers mentioned under a), and e) optionally, one or more water-soluble polymers; polymerizing an aqueous monomer solution comprising drying the resulting polymer; optionally grinding the dried polymer and optionally sieving the ground polymer; optionally surface postcrosslinking the dried, optionally ground and optionally sieved polymer, Adding X-ray amorphous aluminum hydroxide powder after drying, grinding or sieving, and during or after the surface postcrosslinking step if a surface postcrosslinking step is performed, and adding 0.1% to 10% by weight of water based on the amount of polymer before adding the x-ray amorphous aluminum hydroxide powder, after adding the x-ray amorphous aluminum hydroxide powder; Water is added to the superabsorbent in at least three portions, method.

2. 10. The method of claim 1, wherein the second and subsequent portions of water are added after a time of at least 1 second from the addition of the previous portion.

3. 3. The method according to claim 1 or 2, wherein 0.01% to 1% by weight of x-ray amorphous aluminium hydroxide is added, based on the amount of polymer before addition.

4. 4. The method of claim 3, wherein 0.1% to 0.5% by weight of x-ray amorphous aluminum hydroxide is added based on the amount of polymer before addition.

5. 5. The method according to claim 1, wherein the dried, optionally ground and optionally sieved polymer is surface postcrosslinked with a postcrosslinker which forms covalent bonds with polar groups on the surface of the superabsorbent particles.

6. A method for manufacturing an article for absorbing a fluid, comprising the steps of: Producing a superabsorbent by the method according to any one of claims 1 to 5; manufacturing an article for absorbing fluid comprising said superabsorbent; A method comprising:

7. 1. A method of making an article for absorbing fluid, comprising the steps of: The method comprises the steps of producing a superabsorbent according to any one of claims 1 to 5, A method, wherein the manufacture of an article comprises the step of adding said superabsorbent.

Citation Information

Patent Citations

  • Super absorbent resin composition

    JP2017509757A